PWE-100 Missed Rates of Colorectal Cancer - Diagnostic Limitations. (17th August 2016) - Clarke, E; Woolson, KL; Saunders, M; Millington, J; Armstrong, M; Metzner, M
Abstract : Introduction: Colorectal cancer is the fourth most common cancer in the UK and the second leading cause of cancer related deaths. Missed colorectal cancer may delay diagnosis and treatment and lead to worse disease outcome. Colonoscopy is considered the gold standard in diagnosis of colorectal cancer but increasing numbers of computed tomography (CT) scans are performed as a less invasive alternative. Other cross-sectional modalities are also used to examine the abdomen.Our aim was to determine the rate of missed colorectal cancers at initial investigation (endoscopy or CT) amongst patients subsequently diagnosed with colorectal cancer in 2014. Methods: We identified all colorectal cancer diagnoses made in 2014 by interrogating the histopathology system. Review of the electronic records detected any endoscopic investigations or cross sectional imaging in the 2 years before diagnosis. All CT imaging within 2 years of diagnosis was reviewed by a consultant gastrointestinal radiologist. Results: There were 226 diagnoses of colorectal cancer in 2014. 3 patients had a colonoscopy within 2 years of diagnosis which did not demonstrate the lesion, ie 3 interval cancers. Median delay to diagnosis was 18 months. All 3 were right sided cancers. 11 patients underwent cross-sectional imaging in the 2 years prior to diagnosis which did not reveal the lesion, of whom 8 had multiple scans. Median delay to diagnosis was 9 months.No patients developed an interval cancer following a CTC. Conclusion: CT is not a reliable investigation to rule out colonic malignancy and clinicians may be falsely reassured by a negative result. We suggest that all patients in whom Colorectal cancer is suspected should be investigated when appropriate using either endoscopy or CTC, regardless of any other recent imaging. References: 1 Bowel Cancer Key Stats. Cancer Research UK, Nov 2014. www.cruk.org/cancerstats 2 http://nww.irefer.nhs.uk/adult/#Tpc39, accessed 11/7 /15. 3 Leaper M, et al . Reasons for failure to diagnose colorectal carcinoma at colonoscopy. Endoscopy 2004;36 :499–503. 4 Bessler, et al . Rates of new or missed colorectal cancers after colonoscopy and their risk factors: a population based analysis. Gastroenterology 2007;132 :96–102. 5 Guidelines for colorectal cancer screening and surveillance in moderate and high risk groups (update from 2002). Gut 2010 ;59:669–690. 6 Laiyemo AO, et al . Liklihood of missed and recurrent adenomas in the proximal versus the distal colon. Gastrointest Endosc 2011;74 :253–261 7 Patai, et al . Serrated pathway; alternative route to colorectal cancer. World Journal of Gastroenteroloy 2013;19 (5); 607–615. 8 Brenner, et al . Protection from Right- and Left-sided colorectal neoplasms after colonoscopy: Population-based study. Journal of the National Cancer Institute 2010;102 (2):89–95. Disclosure of Interest: None Declared